Seeing shellfish from the seashore: The importance of values and place in perceptions of aquaculture and marine social–ecological system interactions. (December 2015) - Murray, Grant; D'Anna, Linda
Abstract: In increasingly crowded and contested marine and coastal spaces, there is a pressing need to identify the values, context, culture and other factors that shape what activities will be resisted, tolerated, or desired in those spaces. The concept of wellbeing provides a useful analytical lens to address this need. This study characterizes the impact of shellfish aquaculture on local residents in Baynes Sound, British Columbia across environmental, economic and experiential dimensions by creating an overall index of attitudes towards the industry. Findings suggest that perceptions of impacts within the environmental and experiential dimensions are connected, while the economic dimension is somewhat distinct. Attitudes towards the industry were also widely variable within the sample, and the most important predictor variables of attitudes are not those related to common narratives about groups who 'like' or 'dislike' the industry. Rather, these variables are related to general environmental beliefs and place (local community of residence). These findings have important management implications as they demonstrate that local contextual (cultural and other) boundaries have critical influences on any assessment of well-being, how it is defined, and its relationship to marine coastal zone activities like aquaculture. Highlights: Characterizes impacts of shellfish aquaculture on well-being of local communities. Perceived impacts influenced by underlying environmental beliefs.